Recognizing postmodern intersectional identities in leadership for early childhood. Issue 1 (2nd January 2016) - Nicholson, Julie; Maniates, Helen
Abstract : Current interest in the development of leadership capacity within the early childhood profession provides an important opportunity to critically examine our field's conceptualizations of leadership. Modernist binary leader/follower conceptions are not reflective of contemporary scholarship describing identities as multiple, dynamic, socially constituted, negotiated, complex and like the self, undergoing continuous transformation. Additionally, linear descriptions of leadership development contrast with research documenting professional growth and change as a nonlinear, cyclical, and contextually influenced process, and deny the existence of power relationships that afford and constrain the multiple and intersecting identities of practitioners in the early childhood field. Drawing on a multilevel model of intersectionality, we problematize how identities are described in discussions of early childhood leadership and propose the need to revisit, revise, and reimagine leadership concepts for our field by advancing a postmodern turn in our theorizing.